Analysis of the Determination of Water Prices in Subak Dangin Yeh Giri Emas Village, Sawan District, Buleleng Regency - MAHADIKARA, KADEK YARDI; SUDARMA, I MADE; DJELANTIK, A.A. AYU WULANDIRA SAWITRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.8, No.2, April 2019DO - 10.24843/JAA.2019.v08.i02.p01, 2019)
Analysis of the Determination of Water Prices in Subak Dangin Yeh Giri Emas Village, Sawan District, Buleleng Regency Subak Dangin Yeh is one of the subaks which describes the decrease in the availability of surface water. The application of conventional rice planting systems along with the decreasing availability of water causes the use of water to be effective and efficient. Therefore this research becomes important to do. This research was conducted from January to April 2018 with the aim to find out the subak fees charged to farmers, the value of water that farmers use in achieving maximum chargeprofits and water prices that reflect the value of sustainable water use. The scope of this research is the determination of the water price used by farmers with quantitative calculation methods. The data were obtained through library research, direct observation, and in-depth interviews. The population of this study was all subak members with a sample of 50 respondents and determined by the Simple Random Sampling method. Subak fees charged to farmers amounting to Rp.760,000.00 / land / year. Based on VMP analysis, the value of water used by farmers in achieving maximum profits was Rp. 379,932.43 / ha / planting season. The price of water that reflects the value of sustainable water use for groundwater irrigation was Rp.4,693.64 / m3 which consists of a full supply cost of Rp. 160.92 /m3, opportunity costs of Rp. 4,199.14/ m3, and a depletion premium of Rp.333,59 / m3. This price must be paid by farmers in an effort to maintain water resources to remain sustainable in the future.